Handbook of Solar Cell and Photovoltaics Technology - Schindler, Essence, author 647691; Mcintosh, Phoenix, author 647944 (Delhi, India : College Publishing House, 2012)
This is an exhaustive handbook of Solar Cell and Photovoltaics Technology.